Effective Treatment of Nutrients by Adsorption onto the Surface of a Modified Clay and a Toxicity Evaluation of the Adsorbent - Lee, Soonjae; Kwon, Kyu-Sang; Ryu, Jae-Chun; Song, Mi-Kyung; Pflugmacher, Stephan; Park, Chanhyuk; Lee, Sang-Hyup; Park, Chul-Hwi; Choi, Jae-Woo (Kluwer Academic Publishers, 2015)
A pure clay ball and surface-modified clay ball were investigated to remove phosphate from synthetic wastewater; phosphate causes eutrophication in hydro-ecological systems. Adsorption tests of phosphate from aqueous solutions onto two types of adsorbents were conducted. The maximum phosphate adsorption capacities of the pure and surface-modified clay ball were found to be 0.084 and 8.869 mg/g, respectively. In a fixed-bed column packed with surface-modified clay balls, the first breakthrough of phosphate appeared after approximately 4000 min. In addition, the phosphate adsorbed on the surface-modified clay ball was effectively desorbed using a 1 M zirconium sulfate solution, and the adsorbent was regenerated for four adsorption and three desorption cycles by maintaining the adsorption capacity at the value before regeneration. X-ray diffraction (XRD), scanning electron microscopy (SEM)/energy-dispersive X-ray spectroscopy (EDX), and Brunauer-Emmett-Teller (BET) analysis method were performed to reveal the characteristics of the surface-modified clay ball. Cytotoxicity experiment was conducted on the developed adsorbents, and as a result, these showed low cytotoxic effect on the human cells. These results indicated that the surface-modified clay ball, due to the low cost, high adsorption capacity, and non-toxicity, has the potential to be utilized in the cost-effective removal of phosphate from aqueous solutions.